Minimized Disaster Risk on Multifunction Building through Behavior Analysis Prediction, Density and Usage Movement Inside The Building - Mahendra Wardhana (IPTEK Journal of Proceedings Series, 2017)
The number of disasters that struck the building is influenced by various factors. Important factors are often the cause is such as natural disasters, high accelerated and suddenly activity, the magnitude of the circulation that supports, as well as the availability of other supporting facilities in the building. The density of the building is the focus of major concern in minimizing the number of victims in the building when the disaster occurred. Increasing accidents victims may occur due to tightness when the evacuation or in an attempt to escape. Efforts to minimize such casualties into account the circumstances of users of the building. One alternative in predicting users building density and the flow of circulation are the ESVA (Environmental Socialization Value Analysis) analysis method. This method calculated the number of users and resources to support the building. Mark or grade obtained will illustrate the high risk of accidents can happen. Factors that will be analyzed in this ESVA method related to activity and socialization activities that occur in it. User activity in the building related to its users behavior patterns. Finally, the ESVA development through deepening the analysis of user socialization behavior patterns of the building will increase the accuracy of victim risk prediction disaster in buildings.